Relation between time-domain chargability and spectral chargability in an IP survey conducted by an exploration company in the high sector Checa, Valley of Tambo Arequipa, 2015 - Peláez Mc Evoy, Ricardo Fabian (2021)
Geophysical studies oriented to characterization play a very important role in providing a better understanding of the internal structure of the earth and specifically of a new study area and consequently being able to map its properties, its characteristics and the effects generated by the processes of geological alteration. This will finally generate a better geological - geophysical interpretation in the new study zone. In this research work the chargeability data registered in the time domain is being used, firstly the values registered through the 20 windows sampled in time are used and this decay curve obtained is the one used to determine the function transfer that expresses the behavior of the subsoil when applying a current and observing its chargeability. This transfer function is then used, and the Fourier transform is applied to decompose this new signal into its spectral values. These spectral values extracted from the transfer function contain values of amplitude, phase, and angular frequency. With these new variables, 3 additional cubes have been generated and this has made it possible to have more elements and variables that help in a better characterization and interpretation of the study area. The important thing about this research work is the way in which the data recorded over time is used and through a Fourier transform it is changed to the spectral domain that have sensitive characteristics for each type of rock or soil. This has allowed us to understand how a medium behaves when an electric field is applied to it and through these results, we can give an added and additional value to the chargeability data recorded over time. Everything mentioned above has been achieved using a series of algorithms that have been developed in MATLAB to finally obtain the variables angular frequency, amplitude, and phase. Finally, these results are observed with better clarity with the variable amplitude where a differentiation can be observed between a type of massive rock, a fractured rock, alteration zones and zones of low compaction. Regarding the phase variable, a differentiation of blocks with a good alignment of the fault can be confirmed, confirming the bearing and azimuth of the fault.